2018
DOI: 10.1007/s10877-018-0174-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain intensity monitoring with the classification of multiple physiological parameters

Abstract: Current acute pain intensity assessment tools are mainly based on self-reporting by patients, which is impractical for non-communicative, sedated or critically ill patients. In previous studies, various physiological signals have been observed qualitatively as a potential pain intensity index. On the basis of that, this study aims at developing a continuous pain monitoring method with the classification of multiple physiological parameters. Heart rate (HR), breath rate (BR), galvanic skin response (GSR) and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 43 publications
3
61
1
1
Order By: Relevance
“…The facial sEMG was recorded among other biosignals including heart rate, respiratory rate and skin conductance. The procedures are described and reported with greater detail in Jiang et al [31]. The study procedures were conducted in a quiet room with a comfortable armchair.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The facial sEMG was recorded among other biosignals including heart rate, respiratory rate and skin conductance. The procedures are described and reported with greater detail in Jiang et al [31]. The study procedures were conducted in a quiet room with a comfortable armchair.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The study subjects may have applied different emotion regulation strategies during pain inducement that can moderate their pain expression [57]. However, in addition to facial electrodes, the participants wore electrodes on their fingers and in a belt around their chests to detect other biosignals (Reported by Jiang et al [31]). This might have distracted them from concentrating on the facial expressions only.…”
Section: Limitationsmentioning
confidence: 99%
“…Although several commercially devices [2,8,9], as well as newly researched principles [10,11], are currently available and clinically evaluated in many trials, no monitor is widely and routinely used for analgesia assessment [12]. Hence, what differentiates Anspec-pro from the other available devices is the mathematical formalism for parametric modelling of time-frequency variations of skin impedance values [13].…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of medication on pain is generally evaluated as the degree of decrease in patients' subjective pain ratings after treatment. Although self-report is still the golden-standard for pain assessment in clinical practice, a variety of physiological correlates of pain have been found in past decades [15][16][17] . Particularly, a huge body of studies based on electroencephalography (EEG) have shown that pain perception is closely associated with certain types of brain rhythmical activities [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%